PENGARUH NARSISME MAHASISWA TERHADAP KEPUASAN MENGGUNAKAN APLIKASI TIKTOK - Sapari, Yusuf; Suhara, Rizki Budhi; Alfionita, Monica (Jurnal Ilmu Komunikasi Acta Diurna, 2023)
The TikTok application is used by users to upload videos of themselves which are then shared with other users of the TikTok application. This application is a music player that uses lip-sync technology and has a maximum play time of 15 to 60 minutes. In 2018 the most applications were submitted for TikTok, totaling 45.8 million. This includes apps like YouTube, Instagram, Whatsapp, Twitter, Facebook and Messenger. This study aims to examine the effect of student narcissism on satisfaction using the tiktok application. Data collection was carried out by distributing questionnaires to 60 respondents. Data analysis used normality test, linearity test, simple linear regression test, coefficient of determination (R2). In order to get the right results, it is done by testing the hypothesis (t). The t test aims to determine the effect of each narcissism variable (X) significantly on the satisfaction variable (Y). The results showed that accepting all hypotheses namely student narcissism (X) has a significant linear effect on satisfaction (Y). If X1 is not carried out, student narcissism towards satisfaction using the TikTok application will experience dissatisfaction. Conversely, if X1 is carried out, student narcissism towards satisfaction using the TikTok application will experience increased satisfaction.